Bauran Promosi Jasa Perpustakaan (Studi Evaluasi Model CIPP pada Bauran Promosi di UPT Perpustakaan ISI Surakarta Tahun 2010-2014) - Karminah, Wahyu (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
The objective of research was to reveal that what context, input, process and product were in relation to promotion mix in Library Technical Service Unit (UPT Perpustakaan of ISI Surakarta). This research was intended to find out whether or not the condition of context, input, process and product in promotion mi was consistent with CIPP Norm. This study was conducted in Indonesian Art Institute (ISI) of Surakarta. The research methodology applied was evaluation one using CIPP (Context, Input, Process and Product) evaluation model. Data of Context, Input, Process and Product was collected using qualitative approach. The user’s response to product produced was confirmed with quantitative data collected through distributing questionnaire to 97 respondents. The informants consisted of librarians, IT (Information Technology) centre staffs, studentsand lecturers. There were three types of promotion mix was conducted by Library of Surakarta ISI: user education, Book Exhibition, and Internet. The result of research showed that the implementation of program has been consistent with expectation. The result of research was expected to be used as reference in new promotion program plan in the next period